2022
DOI: 10.3390/ijms231810221
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on the Roles of PCSK-9 Inhibitors in the Management of Acute Ischemic Stroke Patients

Abstract: Acute ischemic stroke (AIS) represents an important cause of disability and death. Since only a minor percentage of patients with AIS are eligible for acute therapy, the management of risk factors is mandatory. An important risk factor of AIS is hyperlipemia. The current guidelines recommend a strict correction of it. Statins are recommended as the first-line treatment, while proprotein convertase subtilin/kexin type 9 (PCSK-9) inhibitors are administered as a second or even third option when the goal for a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Conversely, individuals with different genetic causes of heart failure, such as hypertrophic cardiomyopathy (HCM), cardiac amyloidosis, or Fabry disease, already have access to a variety of disease medications (151,152). In addition, two monoclonal antibodies evolocumab and alirocumab have been approved approved by the FDA in 2015 as an add-on to the therapy for heterozygous familial hypercholesterolemia (HeFH) and homozygous familial hypercholesterolemia (HoFH) (153). Furthermore, a number of ongoing clinical studies seek to broaden the use of gene-informed therapy selection, and a number of targeted therapies with associated predictive biomarkers are anticipated to emerge in the near future (Table 6).…”
Section: Future Prospective Of Cvds Therapiesmentioning
confidence: 99%
“…Conversely, individuals with different genetic causes of heart failure, such as hypertrophic cardiomyopathy (HCM), cardiac amyloidosis, or Fabry disease, already have access to a variety of disease medications (151,152). In addition, two monoclonal antibodies evolocumab and alirocumab have been approved approved by the FDA in 2015 as an add-on to the therapy for heterozygous familial hypercholesterolemia (HeFH) and homozygous familial hypercholesterolemia (HoFH) (153). Furthermore, a number of ongoing clinical studies seek to broaden the use of gene-informed therapy selection, and a number of targeted therapies with associated predictive biomarkers are anticipated to emerge in the near future (Table 6).…”
Section: Future Prospective Of Cvds Therapiesmentioning
confidence: 99%
“…2 Roles of PCSK9 in different ischemic stroke-related risk factors 2.1 Role of PSCK9 in lipid homeostasis PCSK9 belongs to the chymosin serine protease mainly synthesized and released by the liver, small intestine, and kidneys (Seidah and Prat, 2012), playing an important role in maintaining the homeostasis of cholesterol. Lots of studies have shown that PCSK9 increases the level of LDL-C in the body by inhibiting the recirculation of the low-density lipoprotein receptor (LDL-R) (Ilut et al, 2022). When LDL-R recognizes and binds to LDL-C, it forms a complex that enters the cell through a lattice-protein heavy chaincoated vesicle and is internalized into endosomes.…”
Section: Introductionmentioning
confidence: 99%